Revitalizing the Role of Kiai in Strengthening Religious Moderation: Case Study of Moderate Islam in Pamulang, South Tangerang - Hasyim, Abd Wahid; Chair, Abd (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study investigates the promotion of religious moderation in Pamulang, South Tangerang, through the revitalization of moderate Islam by Kiai. The research uses a qualitative phenomenological approach and attitude-behavior relationship theory to explore the role of Kiai in fostering religious harmony within the Muslim community and across religious groups in Pamulang's diverse society. Data was collected through literature reviews, documentation, interviews, observations, and Focus Group Discussions (FGD). The findings indicate that Pamulang, while multi-ethnic and culturally diverse, is predominantly Muslim. The revitalization is led by ten charismatic kiai, two locals and eight immigrants, with strong educational backgrounds, both domestic and international, which grant them legitimacy as religious leaders. This revitalization has led to significant changes, with the community shifting from conflicts over religious differences to greater tolerance, attributed to the Kiai's efforts to promote moderate Islam.